The King Danylo Romanovich in Rus’-Mongolian Relations: Discussion Questions of Historiography - Чугуй, Тарас (V. N. Karazin Kharkiv National University Bulletin History of Ukraine. Ukrainian Studies: Historical and Philosophical Sciences, 2019)
The article analyzes topical issues of the Rus’-Mongolian relations of the times of King of Rus’ Danylo Romanovich. The consideration of the discussion aspects of political relations between Rus’ and the Golden Horde in the historiography is analyzed. It is concluded that the impression made by the Mongols on young Prince Danylo during the Battle on the Kalka River prompted him to engage in reforming his own army borrowing from Mongolian tactics and weapons. The establishment of the power of the Galician-Volyn ruler in Kyiv in 1239 caused the Mongol conquerors to seize not only the ancient capital of Rus’, but also the towns Volodymyr and Galich. Danylo Romanovich’s attempts to organize a joint struggle with the Hungarians and Poles against mongols in the 1240s and 1241s failed. Despite the fact that the campaigns of the Mongol troops caused great losses, we consider the hypothesis of the complete desolation of the Rus’ Land to be obsolete and unsubstantiated. At the same time Bolokhivshchyna and Pereyaslavshchyna were under the direct authority of Mongolian officials. Instead, the dependence of the Galich and Volyn lands on the Mongols was nominal because the Romanoviches continued to pursue independent domestic and foreign policies. Danylo’s status as a “mirnik” of Khan Batu facilitated a political alliance with the Hungarian King Bela IV. The political agreement of Danylo Romanovich with Andriy Yaroslavovich caused a sharp negative reaction in the Mongols. After the victory of Nevruy over the Prince of Vladimir-Suzdal in 1252 against Danylo Kuremsa began military action. However, due to the decisive actions of Romanoviches Kuremsa was repeatedly defeated. The confirmation of Danylo Romanovich’s sovereign status was his coronation in the second half of 1253. The last stage of the relations of King of Rus’ Danylo Romanovich with the Mongols took place in the late 50’s – early 60’s of the XIII century. Burundai was able not only to destroy Danyl’s alliance with Lithuania, but also to restore Khan’s dominion over Romanovich’s possessions. It is important to emphasize that Romanovichi remained in the status of “mirnik” not “dannik” as rulers of Northeast Rus’. The absence of the Basques, as well as the transfer by the Mongols of the shortcut to Kyiv to the Vladimir-Suzdal Princes directly dependent on the Golden Horde once again underlines another legal status of the Galician and Volyn Lands.